2022
DOI: 10.1038/s41579-021-00661-1
|View full text |Cite
|
Sign up to set email alerts
|

Biology and evolution of bacterial toxin–antitoxin systems

Abstract: Toxin-antitoxin systems are widespread in bacterial genomes. They are usually composed of two elements: a toxin that inhibits an essential cellular process and an antitoxin that counteracts its cognate toxin. In the past decade, a number of new toxin-antitoxin systems have been described, bringing new growth inhibition mechanisms to light as well as novel modes of antitoxicity. However, recent advances in the field profoundly questioned the role of these systems in bacterial physiology, stress response and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
268
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(304 citation statements)
references
References 233 publications
6
268
0
Order By: Relevance
“…The next most represented defense genes in deletions were those involved in TA systems (Fig. 6b), which can also act as an antiphage system (78). Recent experimental work has demonstrated that mobility and rapid turnover of genes involved in intracellular defense machinery are essential mechanisms to maintaining the core genome in the face of phage predation (79).…”
Section: Discussionmentioning
confidence: 99%
“…The next most represented defense genes in deletions were those involved in TA systems (Fig. 6b), which can also act as an antiphage system (78). Recent experimental work has demonstrated that mobility and rapid turnover of genes involved in intracellular defense machinery are essential mechanisms to maintaining the core genome in the face of phage predation (79).…”
Section: Discussionmentioning
confidence: 99%
“…It made sense we found phage protection functions on our Acinetobacter plasmids, as plasmid-encoded phage defense systems is a known strategy for combating phage infection 76,77 . We also found cell wall metabolism functions.…”
Section: Discussionmentioning
confidence: 96%
“…Finding replication and mobility proteins was expected as they form the backbone of plasmids, however finding several TA systems was not expected. TA systems can be thought of as selfish genetic elements, securing the stability of the plasmid carrying it through post-segregation killing 78 . It could be speculated that the relative abundance of TA systems correlates to the small size distribution of our plasmids.…”
Section: Functional Domains In Sewage Plasmidomesmentioning
confidence: 99%
“…Toxin-antitoxin (TA) systems are genetic modules that are frequently found on bacterial chromosomes and plasmids ( Pandey and Gerdes, 2005 ; Leplae et al, 2011 ; Harms et al, 2018 ; Srivastava et al, 2021 ; Jurėnas et al, 2022 ). TA systems typically consist of two factors: a toxin protein that has an inhibitory or poisonous effect on the host organism and an antitoxin that either counteracts expression of the toxin or antagonizes toxin activity ( Page and Peti, 2016 ; Harms et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, under particular stress conditions, the toxin may overcome the neutralizing effect of its cognate antitoxin, which eventually leads to a targeted inhibition or poisoning of an essential biosynthetic process. Various aspects of the bacterial lifestyle are associated with expression of toxins from TA systems including (i) genome stability, (ii) phage defense, (iii) stress adaptation, and (iv) persister formation ( Wang and Wood, 2011 ; Page and Peti, 2016 ; Harms et al, 2018 ; Fraikin et al, 2020 ; Song and Wood, 2020 ; Jurėnas et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%